Inter-session Reliability of Magnetic Nerve Stimulation and Within-Session comparison to Electrical Nerve Stimulation in Evaluating Neuromuscular Function of Knee Extensor Muscles - Romina Ledergerber; Martin Keller (Current Issues in Sport Science)
Introduction Quantifying neural activation is crucial for evaluating rehabilitation progress and adaptations following resistance training. A commonly used method for assessing voluntary activation (VA) is the Interpolated Twitch Technique with electrical nerve stimulation (ENS). However, this method is often associated with discomfort, limiting its applicability in sensitive populations such as children or patients (Shield & Zhou, 2004). Magnetic nerve stimulation (MNS) offers a painless and promising alternative, but its validity and reliability remain insufficiently established (Verges et al., 2009). This study aims to address this gap by comparing ENS and MNS and assessing the reliability of MNS across sessions.